Performance Comparison of Turbo coder and low-density parity check codes - et. al., Mrs. Channaveeramma. E , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless communication systems will suffer from the noise introduced in the channels. Channel codes are the essential part of wireless communication systems which help in detection and correction of errors due to the noise introduced in the channel. Turbo codes and LDPC codes are the Forward Error Correction (FEC) channel coding techniques which have the error correcting capability near to Shannon codes along with improvement in transmission rate and energy efficiency.Turbo codes were introduced in 1993[1]. LDPC codes were discovered in 1960 by R.Galleger in his Ph.D dissertation at MIT.They became implementable, after the discovery of Turbo codes[2]. The satellite communications such as DVB-RCS, telecommunications such as 3G, 4G, Wireless metropolitan standards IEEE 802.16(WiMax) uses turbo codes[3]. G.hn/G.9960 (ITU-T standard for networking over power lines, phone lines and coaxial cable), 802.3 an(10GBps ethernet over twisted pair), CMMB(China multimedia mobile broadcasting), DVB-S2/DVB-T2/DVB-C2(Digital video broadcasting , second generation), DMB-T/H(Digital video broadcasting), Wimax(IEEE 802.16e standard for microwave communications), 802.11n-2009(wi-Fi standard) are the few standards where the LDPC codes are employed.[4]